Neurodevelopmental subtypes of bipolar disorder are related to cortical folding patterns: An international multicenter study - Sarrazin, Samuel; Cachia, Arnaud; Hozer, Franz; McDonald, Colm; Emsell, Louise; Cannon, Dara M; Wessa, Michele; Linke, Julia; Versace, Amelia; Hamdani, Nora; D'Albis, Marc‐Antoine; Delavest, Marine; et al. (Bipolar disorders, 2018)
Objectives Brain sulcation is an indirect marker of neurodevelopmental processes. Studies of the cortical sulcation in bipolar disorder have yielded mixed results, probably due to high variability in clinical phenotype. We investigated whole‐brain cortical sulcation in a large sample of selected patients with high neurodevelopmental load. Methods A total of 263 patients with bipolar disorder I and 320 controls were included in a multicentric magnetic resonance imaging (MRI) study. All subjects underwent high‐resolution T1‐weighted brain MRI. Images were processed with an automatized pipeline to extract the global sulcal index (g‐SI) and the local sulcal indices (l‐SIs) from 12 a priori determined brain regions covering the whole brain. We compared l‐SI and g‐SI between patients with and without early‐onset bipolar disorder and between patients with and without a positive history of psychosis, adjusting for age, gender and handedness. Results Patients with early‐onset bipolar disorder had a higher l‐SI in the right prefrontal dorsolateral region. Patients with psychotic bipolar disorder had a decreased l‐SI in the left superior parietal cortex. No group differences in g‐SI or l‐SI were found between healthy subjects and the whole patient cohort. We could replicate the early‐onset finding in an independent cohort. Conclusions Our work suggests that bipolar disorder is not associated with generalized abnormalities of sulcation, but rather with localized changes of cortical folding restricted to patients with a heavy neurodevelopmental loading. These findings support the hypothesis that bipolar disorder is heterogeneous but may be disentangled using MRI, and suggest the need for investigations into neurodevelopmental deviations in the disorder.